Strongly C_11-Condition Modules and Strongly T_11-Type Modules - Hadi, Inaam M A; Shyaa, Farhan D (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
In this paper, we introduced module that satisfying strongly -condition modules and strongly -type modules as generalizations of t-extending. A module  is said strongly -condition if for every submodule of  has a complement which is fully invariant direct summand. A module   is said to be strongly -type modules if every t-closed submodule has a complement which is a fully invariant direct summand. Many characterizations for modules with strongly -condition for strongly -type module are given. Also many connections between these types of module and some related types of modules are investigated.